Етюди про Шевченка – апогей літературно-критичної шевченкіани Михайлини Коцюбинської - Коруняк, Юлія; Koruniak, Yulia (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано основні положення монографії видатного літературного критика, літературознавця М. Коцюбинської «Етюди про поетику Шевченка», визначено її місце в контексті літературно-критичної спад¬щини вченої. Простежено своєрідність науково-критичної рецепції феномену Шевченкового поетичного слова М. Коцюбинською. The article analyzes the main provisions of the monograph of the outstanding literary critic M. Kotsyubynska «Studies on Shevchenko’s poetics». It is determined its place in the context of literary-critical scientific heritage of the scientist. It is also traced the peculiarity of scientific and critical reception of the phenomenon of Shevchenko`s poetic heritage by M. Kotsyubynska. Through the prism of literary and critical views of scientist the article studies folklore and literary relations in the works of Taras Shevchenko: it is interpreted conditioning of Shevchenko`s poetics by folk component; it is developing a thesis on the relationship of folk songs and lyrics of the artist and his creative rethinking of folk motifs, themes, tools; it is determined the means of folk mastering by poet.
Studies About Shevchenko is the Apogee of Literary-critical Shevchenkiana of Mykhailyna Kotsyubynska
Keywords: Т. Шевченко; літературно-критична рецепція; наукова інтерпретація; фольклор; народна пісня; T. Shevchenko; literary-critical reception; scientific interpretation; folklore; folk song